Analisis Kualitas Website Universitas Khairun Menggunakan System Usability Scale (Sus) - Muhammad, Miftah; Hizbullah, Imam; Mabud, Zulaihah (Fakultas Teknik Universitas Khairun, 2024)
Abstract This study analyzes the quality of the Khairun University website (unkhair.ac.id) using the System Usability Scale (SUS) method. SUS is an evaluation method consisting of 10 statements that assess effectiveness, efficiency, and user satisfaction. Data were collected by distributing questionnaires to 200 respondents who were students from 10 faculties at Khairun University. The results showed an average SUS score of 64.3, which places the quality of the website at grade